Motivations, income determinants and livelihood vulnerability of female teenage head porters in Kasoa, Ghana - Otieku, E.; Ackah, C.; Forkuor, D. (Emerald Publishing Limited, 2017)
Purpose – The purpose of this paper is to provide statistical and empirical evidence on the motivations, income determinants and livelihood vulnerabilities of female teenage head porters. The paper draws from the motivational theory and the livelihood vulnerability approach to assess the motivations, livelihood vulnerabilities and income determinants of female teenage head porters in Kasoa, Ghana. Design/methodology/approach – The mixed methods data collection instruments were used to collect primary data from 200 randomly sampled female teenage head porters in Kasoa. It includes both close and open-ended questionnaires, one case study and personal observation. Findings – Based on the estimation, the study found that household poverty, unemployment, desire for regular income and quest for personal independence were significant motivational factors drawing teenage girls into head porting. Also, age of respondents and years of experience in the occupation were the significant determinants of income of respondents. Exposure to frequent malaria, stress and physical pains were common livelihood risk factors faced by the respondents. Majority of them were from the northern region of Ghana and less than 20 percent of them had formal education. Practical implications – The paper proposed for extensive implementation of robust macroeconomic and specific social protection interventions to enhance equal job and income opportunities as well as to protect the vulnerable. Originality/value – The study provides statistical and empirical results different from other related studies (Opare, 2003; Awumbila, 2007; Baah-Ennumh et al., 2012; Akanle and Chioma, 2013).
Keywords: Women; Vulnerability; Income; Livelihood